Perilaku Manajemen Keuangan Syariah: Implikasi Pengendalian Resiko Keuangan Tinjauan Tafsir Al-Mukminun - Arafah, Santi; Tarigan, Azhari Akmal; Syahreza, Rahmi (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2025)
This research aims to discuss Q.S Al-Mukminun regarding the concept of Islamic financial management behavior in financial risk control. This research is qualitative with a library research approach, namely the data used in this research comes from various literature books, journals, dictionaries, encyclopedias, and other documents related to the object of this research. This data analysis includes activities, namely categorizing data, organizing data, manipulating data, summing up data directed at obtaining answers to research problems. The method used to analyze the data in this research is deductive method and comparative method. The results of this study explain that the interpretation of Q.S Al-Mukminun explains the characteristics of believers who can bring happiness in this world and the hereafter, especially in addressing financial problems related to sharia financial management behavior. good sharia financial management behavior leads to good financial decision making as well, especially in allocating funds as savings which in turn can be used as initial capital in starting a business